Strategi Kebijakan Fiskal Pada Industri Minyak Dan Gas Bumi Dengan Pendekatan Kebijakan Rezim Gross Split Dan Rezim Production Sharing Contract Cost Recovery (Studi Kasus Pada PT. Apexindo Pratama Duta Tbk.) - Zaneta Cahaya Fitri; Budi Wahono; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
AbstractOil and gas exploration and production activities are a strategic and potential industry for the Indonesian people. The availability of oil and gas as an energy source is one of the main factors in increasing a nation's income. In 2017, the cost recovery scheme was changed to gross split. The background for changing PSC cost recovery to gross split is because cost recovery is considered ineffective and inefficient. Therefore, a study was conducted which aims to determine the fiscal analysis used by the government in regulating oil and gas with the gross split regime approach and PSC cost recovery and to find out which is more profitable between the two methods used, namely PSC cost recovery and gross split. The fiscal analysis carried out by the government in oil and gas exploitation in Indonesia is to divide the fiscal terms for the two regimes, cost recovery and gross split, so that the take taken by the government and contractors is not mutually beneficial and fair. As well as comparing cashflow schemes between cost recovery and gross split, as well as conducting an economic analysis to obtain the results of which scheme is more feasible to be applied in Indonesia. Keywords: Production Sharing Contract, Gross Split, Cost Recovery, Fiscal Terms